Defining factors promoting successful virtual elementary school nutrition education: lessons learned during the pandemic - Marie Balfour; Joseph Benbow; Bethany Korom; Leslie Ruffalo; Bryan Johnston (Humanities & Social Sciences Communications)
Abstract As obesity rates continue to rise, comprehensive nutrition education for children needs to be further expanded and optimized. Due to the COVID-19 pandemic, more virtual nutrition programs emerged to bridge the gap of social distancing and continue health education endeavors remotely, but there is conflicting data on preferred formats and elements that make these innovative programs most impactful. To identify community and pedagogical factors that define successful virtual elementary school nutrition education partnerships between academic medical centers and elementary schools, an existing in-person nutrition program in Milwaukee County was adapted to a virtual format during the COVID-19 pandemic. The first virtual learning program was conducted wIth 3rd grade students (N = 109) at two urban Milwaukee County elementary schools during the school year, and the second was conducted with students and families (N = 7) from the same schools during the summer with live virtual cooking sessions and farmers market stipends. Focus group discussions from teachers (N = 7) and families (N = 8) and nutritional knowledge quizzes from students (N = 80) were obtained. Statistical analysis of student quizzes revealed significantly lower nutritional knowledge after lessons were completed as compared to previous in-person lessons. Content analysis of focus groups revealed three main themes surrounding successful nutrition program implementation: support, community, and engagement. Support, community, and engagement should be leveraged synergistically to increase participant interaction with nutrition topics and drive successful elementary school health education programs.